INTERJEKSI DALAM NOVEL DONYANE WONG CULIKA KARYA SUPARTA BRATA [Interjection in the novel Donyane Wong Culika by Suparta Brata] - Siti Komariyah (TOTOBUANG, 2016)
Interjection is a word used to express the feelings of the speaker. This interjection used by the author of the novel to convey the emotion or feeling that not only portrayed through the words or sentences, but also it could be delivered with the other forms of the words that interjection. The study entitled "Interjection of the novel Donyane Wong Culika' by Suparta Brata aimed to describe the forms and functions of the interjection used in the novel Donyane Wong Culika. This study was descriptive qualitative research. The research data obtained by the simak method and the note technique. These results indicate that the novel Donyane Wong Culika were two forms of the interjection: (1) primary, namely o, e, ah, lo, lha, wo, wah, heh) and (2) secondary, the form of the words, repetitionof words and phrases. The secondary interjections were alah, alaah, adhuh, wadhuh, oallah, wo lha, e lha kok, la kok, lha wong, adhuh-adhuh, mak cles, ora lidhok, astagfirullah!, astaga. The interjections forms in the novel Donyane Wong Culika have the function to express a sense of disappointment, upset, surprised, angry, shocked, awe, amazement, fear, marking the meaning of underestimate, marking remembered something. Interjeksi adalah kata yang digunakan untuk mengungkapkan perasaan pembicara. Interjeksi ini digunakan oleh penulis novel untuk menyampaikan emosi atau perasaan yang tidak hanya digambarkan melalui kata-kata atau kalimat, namun juga dapat disampaikan dengan bentuk kata yang lain yaitu interjeksi. Penelitian yang berjudul ‘Interjeksi dalam Novel Donyane Wong Culika’ Karya Suparta Brata ini bertujuan untuk mendiskripsikan bentuk-bentuk dan fungsi interjeksi yang digunakan dalam novel Donyane Wong Culika. Penelitian ini adalah penelitian deskriptif kualitatif.  Data penelitian diperoleh dengan metode simak dan  teknik catat. Hasil penelitian ini menunjukkan bahwa dalam novel Donyane Wong Culika  terdapat  2 bentuk interjeksi yaitu (1) primer, yaitu o, e, ah, lo, lha,  lho, wo, wah, heh) dan (2) sekunder, yang berbentuk kata, perulangan kata, dan frasa. Interjeksi sekunder tersebut yaitualah, alaah,adhuh, wadhuh,oallah, wo lha, e lha  kok, la kok, lha wong, adhuh-adhuh, mak cles, ora lidhok, astagfirullah!, astaga. Bentuk interjeksi dalam novel Donyane Wong Culika  memiliki fungsi untuk mengungkapkan rasa kecewa, kesal, heran, marah, kaget, kekaguman, takjub, ketakutan, menandai makna penyangatan, menandai teringat kembali kepada sesuatu.